Pengaruh Lingkungan Kerja, Motivasi dan Kepuasan terhadap Disiplin Kerja pada Karyawan J&T Express Nusukan Surakarta - Anisa Putri Ayudya; Asih Handayani (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The purpose of this study is to examine how work environment, motivation, and job satisfaction influence the discipline of employees at J&T Express Nusukan, Surakarta. This research employed a quantitative approach with purposive sampling, involving seventy respondents. Data were collected through observation, questionnaires, and literature review, and analyzed using multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results indicate that motivation has a significant effect on work discipline, while work environment and job satisfaction show no significant influence. Simultaneously, the three variables contribute 54% to work discipline, while the remaining percentage is explained by other factors not included in this study. The findings suggest that improving employee motivation can positively affect work discipline. However, work environment and job satisfaction alone are not sufficient to enhance discipline, indicating that other factors, potentially related to organizational culture, leadership, or personal characteristics, may also play a significant role. This study contributes to understanding the importance of motivation in fostering employee discipline and provides valuable insights for organizations aiming to improve employee performance.